The hepatitis C virus p7 protein forms an ion channel that is inhibited by long-alkyl-chain iminosugar derivatives. - Pavlović, D; Neville, D; Argaud, O; Blumberg, B; Dwek, R; Fischer, W; Zitzmann, N (National Academy of Sciences, 2003)
We show that hepatitis C virus (HCV) p7 protein forms ion channels in black lipid membranes. HCV p7 ion channels are inhibited by long-alkyl-chain iminosugar derivatives, which have antiviral activity against the HCV surrogate bovine viral diarrhea virus. HCV p7 presents a potential target for antiviral therapy.